Between «Keep Being» and «Becoming Someone»: Bolivians and Second-Generation Bolivians in Argentina - Novaro, Gabriela (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
In this article I expose the results of a work in a location of the Buenos Aires province, inhabited by immigrants from Bolivia and their children and grandchildren, many of them born and raised in Argentina. I present the development of the social-anthropological theory and the migratory studies on descendants and generational transmission. In the light of the categories and debates exposed I analyze situations registered in the fieldwork. I focus on the adult expectations about the identifications of their children, to continue being (bolivians), while being somebody in life and include themselves in Argentina. I underline the need to associate the notion second generation bolivians (in use in the location) both, to stigmatization processes and to collective projects of continuity in situations of mobility and dispossession that challenge the possibilities of generational transmission.